Philippine medical thesaurus on anatomy fluids and secretions and stomatognathis system in Tagalog - Ragunton, Florence U. (2003)
As an initiative from the joint efforts of the Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila, the creation Multilingual Philippine Medical Thesaurus Project serves as a pioneering literature for future development in Philippine medical informatics and information Science. Patterned from the Unified Medical Language System (UMLS) or the U.S. National Library of Medicine, terms were gathered from the Medical Subject Headings (MeSH) for translation to initially, the Tagalog language.